A field study on a programmed therapy for language problems - Burl B Gray (Journal of All India Institute of Speech and Hearing, 1970)
Programming and educational technology represent teaching procedure which maximize the educational outcome by defining and operating a systematic" sequence of the basic learning elements—stimulus, response and consequence. One of the basic considerations in such an instructional equation is the deliberate and correct use of information about human learning. Indeed, the efficacy of teaching strategies which adhere to these principles is well substantiated in the literature. It would appear that any attempt at designing a teaching strategymust incorporate these basic elements. In fact, it is doubtful if it is possible to, avoid it. At the moment the only choice appears to be whether or not to go about it in a systematic way